Building Local Food Security with an Ecological Approach - Judijanto, Loso; Suparwata, Dewa Oka (West Science Agro, 2025)
Building local food security with an ecological approach is vital for ensuring sustainable and resilient food systems, particularly in the face of climate change and socio-economic challenges. This study systematically analyzes 60 peer-reviewed documents from the Scopus database to identify key themes, challenges, and opportunities in this domain. The findings highlight the importance of biodiversity, sustainable land management, governance, and policy support in achieving food security. However, significant barriers such as climate change, socio-economic inequalities, and knowledge gaps impede progress. Emerging technologies, community participation, and targeted policy reforms are identified as pivotal strategies for addressing these challenges. The study concludes that integrating ecological principles into local food systems not only enhances agricultural resilience but also fosters environmental conservation and social equity. These insights offer valuable guidance for policymakers, researchers, and practitioners working towards sustainable food security.